(untitled) (Research, Society and Development, 2023)
Since the emergence of COVID-19 in Wuhan, the pandemic has spread across the world, causing many deaths and affecting millions of people. Meanwhile, hyaluronic acid has been used in orofacial harmonization to fill wrinkles and grooves in the skin. However, the application of dermal fillers such as hyaluronic acid can lead to a rare complication called delayed intermittent and persistent edema (ETIP), which causes swelling and redness in the treated area. The relationship between ETIP, COVID-19 vaccination and orofacial harmonization has been studied by experts who suggest that ETIP may occur and begin after the vaccine is administered. It is important that healthcare professionals are aware of this possible relationship and inform their patients about the risks before carrying out any aesthetic procedure. Therefore, this narrative review of the literature aims to offer a cataloged document on the relationship between ETIP, COVID-19 and hyaluronic acid as a dermal filler in the clinical practice of orofacial harmonization.